2013
DOI: 10.1021/jp310504n
|View full text |Cite
|
Sign up to set email alerts
|

First Principles Design of Dye Molecules with Ullazine Donor for Dye Sensitized Solar Cells

Abstract: We design a series of metal-free donor-π-bridge molecules (denoted VB0–VB4) based on a new donor groupullazine donoras sensitizers for dye sensitized solar cell (DSSC) applications. Density functional theory (DFT) and time-dependent DFT calculations reveal that the physical properties of dyes, including spectral response, light harvesting efficiency, and electron injection rate, are systematically improved by combining ullazine donor to a series of length changing π bridges. Dye VB2 is the best candidate tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
106
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 189 publications
(110 citation statements)
references
References 34 publications
3
106
0
1
Order By: Relevance
“…As seen in Table 4, with the strong electron-withdrawing group moving from the donor part to acceptor part, n c is in this trend: WS-1 (0.034) [ WS-11 (0.031) [ W-12 (0.027), which may lead to a low V oc on WS-11 and WS-12. However, not only the variation in n c for dyes is very small, but also the effect of n c on V oc is relatively smaller than that of the surface dipole moment [46]. Thus, combined the analysis of vertical dipole moment with the number of electrons in conduction band, we conclude that WS-12 can exhibit a higher V oc due to its larger dipole moment than WS-1 and WS-11.…”
Section: Nbo Electron Distribution Analysismentioning
confidence: 84%
“…As seen in Table 4, with the strong electron-withdrawing group moving from the donor part to acceptor part, n c is in this trend: WS-1 (0.034) [ WS-11 (0.031) [ W-12 (0.027), which may lead to a low V oc on WS-11 and WS-12. However, not only the variation in n c for dyes is very small, but also the effect of n c on V oc is relatively smaller than that of the surface dipole moment [46]. Thus, combined the analysis of vertical dipole moment with the number of electrons in conduction band, we conclude that WS-12 can exhibit a higher V oc due to its larger dipole moment than WS-1 and WS-11.…”
Section: Nbo Electron Distribution Analysismentioning
confidence: 84%
“…Furthermore, we made the approximation that the energetics of the dye are not different whether it is in CH 2 Cl 2 solution or attached to TiO 2 lm, which is supported by previous studies performed by Kuciauskas. 27,28 The driving force, D f , can be expressed as 29,30 …”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Organic dyes are the best way to overcome these problems, organic dyes are natural pigments which was extracted from different part of plants such as fruit, flower, wood, and stems. Feng et al 5 have reported metal-free donor-π-bridge molecule has property to transfer the maximum amount of electrons are injected to the conduction band of semiconductor TiO2 suggested that ullazine donor-π-bridge group can be an excellent dye sensitizer for future DSSC applications.Mohr et al 6 have reported anthocyanin dye sensitizers using the hybrid method to find the properties and dynamics of dyes using DFT and TD-DFT. The result showed the anthocyanin has the potential to absorb the near UV region and studied the photoninduced electron from the dye to TiO2.…”
Section: Introductionmentioning
confidence: 99%